Rubber seed processing for value -added latex production in Nigeria - Iyayi, A. F.; Akpaka, P. O.; Ukpeoyibo, U. (Global Journal of Food and Agribusiness Management, 2018)
Little or no attention has been paid to the seeds produced by the rubber tree (Hevea brasiliensis) unknown that it contains valuable oil which has potential industrial application in the production of soap, cosmetics, paints, glazing putty. Not much is known about the method of processing of the seeds from which the oil is derived. In this article, the processing stages for the seeds are presented and discussed. Possible problems that could be encountered during processing and the solutions are offered. It is anticipated that the added value of rubber seed processing would help raise and diversify sources of income for rubber tree farmers with a view to alleviating poverty in Nigeria